Neutrophil-to-lymphocyte ratio as a prognostic marker in highly PD-L1 expressing advanced non-small cell lung cancer patients in first line treatment with pembrolizumab - Gomes, Lídia (2024)
Introduction and objectives: The neutrophil-lymphocyte ratio (NLR) has been proposed to assess advanced stage non-small cell lung cancer (aNSCLC) response to immunotherapy, given the easy availability and low cost. The aim of our study was to evaluate the relationship between NLR at baseline, after the 3rd and 6th treatment cycles, and progression free survival (PFS) and overall survival (OS), in a population with aNSCLC with a PD-L1 expression ≥50% treated with pembrolizumab monotherapy in first line. Methods: We performed a retrospective study of patients with aNSCLC with PD-L1≥50% who were treated with pembrolizumab first line from February 2017 to July 2021. NLR values at baseline and after the 3rd and 6th pembrolizumab cycles were analyzed. Optimal NLR cut-off were determined with respect to OS, by ROC curve. PFS and OS were compared by Kaplan Meyer method and Cox Proportional Hazard model for NLR measures. Results: Sixty-six patients with PD-L1≥50% (51% males, mean age 65.8 ± 11.2 years) were included in the study. The PD-L1 expression was ≥90% in 74% of the patients. NLR≤4 after the 3rd pembrolizumab cycle were associated with a significant improvement in PFS (23.6 vs 4.3 months, p=0.002) and OS (32.9 vs 6.3 months, p=0.022), compared with NLR>4. Discussion and conclusions: In patients with aNSCLC and a PD-L1≥50% receiving frontline pembrolizumab treatment, low NLR values after the 3rd pembrolizumab cycle were associated with significantly longer PFS and OS. This biomarker may thus help identify individuals on pembrolizumab monotherapy who are at greatest risk for disease progression.